Evaluating the performance of stainless steel in microbial electrolysis cells: Hydrogen production and corrosion behaviour - Raba’atun Adawiyah Shamsuddin; Mimi Hani Abu Bakar; Wan Ramli Wan Daud; Byung Hong Kim; Jamaliah Md. Jahim; Wan Syaidatul Aqma Wan Mohd Noor; Rozan Mohamad Yunus; Ibdal Satar; Fabrice Ndayisenga (Center of Biomass & Renewable Energy (CBIORE), 2026)
Microbial Electrolysis Cells (MECs) provide a sustainable route to hydrogen production via microbial electron transfer, while the biocathode enhances affordability and functionality. Stainless steel (SS) is an ideal material for bioelectrochemical systems (BES) due to its high recyclability and corrosion resistance. The chromium content forms a protective, corrosion-resistant layer that promotes beneficial microbial interactions and enhances durability. However, the MEC requires an oxygen-free cathode, which is incompatible with the layer. This study evaluated the corrosion resistance of SS to microbial interactions, also known as microbial-influenced corrosion (MIC). The results from SS are compared with those from carbon steel (CS) and graphite felt (GF), which are standard laboratory electrode materials used as controls. The performance of these biocathodes was assessed in both open-circuit (Co-MEC) and closed-circuit (Cc-MEC) conditions over a 120-day operational period, with a focus on hydrogen production and corrosion resistance against MIC. SS biocathodes exhibited the highest hydrogen production rate (2.33 ± 0.34 LH₂/m². day), outperforming CS by 54% and GF by 1.3%. Additionally, the SS system demonstrated superior chemical oxygen demand (COD) removal efficiency, achieving 45% COD removal, comparable to the GF (44%), whereas CS achieved 38%. The corrosion analysis revealed that the corrosion rate (RM) of CS (0.08 ± 0.08 mm/year) was 86% higher than that of SS and GF (0.03 ± 0.03 mm/year) under Cc-MEC mode. Microbial community analysis revealed a higher abundance of Desulfovibrio, a genus within the sulphate-reducing bacteria (SRB) group, in Co-MEC systems, which contributes to increased corrosion. In contrast, the Cc-MEC system showed an increase in electrochemically active bacteria (EAB), including Pseudomonas, which are known to promote hydrogen evolution and inhibit SRB. This study highlights the need for further research into corrosion-resistant materials and the optimisation of microbial communities.